Comparison of Two Huanglongbing Detection Methods in Samples with Different Symptom Severity: Perbandingan Dua Metode Deteksi Huanglongbing pada Sampel dengan Tingkat Keparahan Gejala yang Berbeda - Sariasih, Yenny; Subandiyah, Siti; Widyaningsih, Sri; Khurshid, Tahir; Mo, Jianhua; Donovan, Nerida (Jurnal Fitopatologi Indonesia, 2024)
Huanglongbing or citrus greening in Asia caused by the pathogen Candidatus Liberibacter asiaticus (CLas) is one of the most devastating citrus diseases worldwide. This disease is one of the causes of decreased citrus production in Indonesia. Symptoms of huanglongbing in citrus plants in the field and greenhouses have different levels of severity. This study was conducted to detect CLas in several types of samples based on leaf symptoms using conventional and real-time PCR (qPCR). Three pairs of primers were used in this study, a pair of Las606/LSS for conventional PCR and two pairs for qPCR, namely Las931/LSS and Lj900F/Lj900R. The results showed that blotchy mottle is the most easily detected symptom of huanglongbing and found in fields and greenhouses. The Lj900F/Lj900R primer pair is more suitable for detecting CLas pathogens using qPCR than Las606/LSS based on the melting curve and Ct value that appear. qPCR detection is more accurate and sensitive even with lower DNA concentrations. The lower limit of Ct value of healthy leaf samples is 34.08. Citrus leaves are considered positive if the Ct value is less than 34.08. Ct value based on severity or scoring between HLB symptomatic leaves from the field and greenhouse showed a significant difference, i.e. the Ct value of symptomatic samples from the field was lower than that of greenhouse samples.